Training on Management and Simple Recording of DKM Funds at Putat Nutug Village Mosque, Ciseeng, West Java: Pelatihan Pengelolaan dan Pencatatan Sederhana Dana DKM Masjid Desa Putat Nutug, Ciseeng Jawa Barat - Nasri, Rifzaldi; Nuraeni; Darmansyah, Dina Febriani; M. Yusuf; M. Ikra (Procedia of Social Sciences and Humanities, 2022)
Putat Nutug Village is a village located in Ciseeng District, Bogor Regency, West Java. The economic dynamics of the community are very diverse, ranging from traders to farmers. However, their business is still limited to capital. Knowledge of financial institutions that are syar'i safe funds is still very lacking. They are more daring to deal with illegal financial institutions even with very high returns. The purpose of this community service is to improve the knowledge and skills of the general public and especially the DKM managers in the village where the service is located in managing mosque funds in a syar'i way, especially in zakat, infaq and alms funds, so that they can be used as a source of financing that can help capital. public. The service method is in the form of direct training to participants on several things related to cash flow recording, to manual ledger making. The result of community service is an increase in knowledge and skills and understanding in managing mosque funds for the better.